A (ciência) política nas aulas de sociologia do ensino médio: um estudo no Instituto Estadual de Educação, Ciência e Tecnologia do Maranhão – IEMA (Unidade Plena Vargem Grande) - BARROS, Romário Silva (2023)
The research presents a discussion on the teaching of topics related to Political Science in High School Sociology classes held at the State Institute of Education, Science and Technology of Maranhão – IEMA (Plena Vargem Grande Unit) with the intention of producing it in collaboration with teachers and students an e-book with political science categories and concepts with theoretical-methodological guidelines to be used as support material in sociology classes. The study is organized into seven sections. The first describes the Introduction, in which we present the theoretical, methodological and organizational choices of the dissertation text. The second section deals with the conceptual foundations of the curriculum, highlighting curricular theories. In the first subsection, we discuss the guidelines for Technical and Professional Education, then, in the second subsection, we present the historical assumptions and organization of pedagogical activities at IEMA. The third section deals with the history of Sociology Teaching in High School, considering the new perspectives on curricular organization presented by BNCC. In the fourth section, we discuss Political Science and the main concepts worked on in High School Sociology classes: Democracy, Citizenship and Social Participation. Then, in the fifth section referring to Methodology, we present in the first subsection the characterization of UP Vargem Grande - IEMA; In the second, the Research Methodology; In the third, the description of the research product, the e-book for use in sociology classes in high school. Then, in the sixth section we describe the Research Product. The main bibliographic sources used were: Apple (2006), Bodart (2021), Bodart; Cigales (2017), Feijó (2020), Forjaz (1997), Keinert e Silva (2010), Lessa (2010), Meucci (2013); Santos (2002), Silva (2015), Valmore (2016). The research procedure method adopted was the Instrumental Case Study. The research subjects were high school Sociology teachers from the Plena Vargem Grande Unit and the students from UP Vargem Grande. The research concluded that the creation of the Educational Product (e-book) that deals with the contents covered in Political Science contributed to expanding the theoretical- methodological repertoire in Sociology classes in High School.